Coated modified positive electrode material, preparation method thereof and secondary battery

The modified cathode material is covered with La-doped MoP and carbon nanotubes, and the problem of low conductivity of the cathode material of traditional lithium-ion batteries is solved, significantly improving the electrochemical performance and structural stability of the battery.

CN119133415APending Publication Date: 2024-12-13ZHUJI PAWA NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411480464.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The electronic conductivity and electrical properties of traditional lithium-ion battery positive electrode materials are relatively low, resulting in insufficient electrochemical performance and ineffective in improving the electrical properties of lithium-ion battery positive electrode materials.

Method used

The composite material of La doped MoP and carbon nanotubes is coated and modified. The positive electrode material of La doped MoP and carbon nanotubes is prepared by sintering and stirring, forming a more stable interface structure and Higher conductivity.

Benefits of technology

The initial discharge capacity, rate performance and cycling performance of the battery are significantly improved, and the structural stability and electrochemical performance of the positive electrode material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133415A_ABST
    Figure CN119133415A_ABST
Patent Text Reader

Abstract

The invention provides a coated modified positive electrode material which comprises a positive electrode material matrix and a coating layer located on at least part of the surface of the positive electrode material matrix, and the coating layer is a composite material of La-doped MoP and carbon nanotubes. The modified positive electrode material is coated with the La-doped molybdenum phosphide and carbon nanotube composite material, so that the initial discharge capacity, the rate capability and the cycle performance of the battery can be obviously improved. The invention also provides a preparation method of the coated modified positive electrode material and a secondary battery based on the coated modified positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of positive electrode materials for lithium ion batteries, and in particular relates to the modification of positive electrode materials. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, power vehicles, aerospace and other fields due to their high energy density and long cycle life. In order to improve the electrochemical performance of lithium battery positive electrode materials, the commonly used method is to dope or surface-coat the above positive electrode materials.

[0003] Traditional doping and coating materials are mostly ZrO 2 ,MgO,TiO 2 , WO 3 Oxides such as these, these coating materials can not only improve the partial conductivity of the positive electrode material, but also inhibit the interface reaction between the electrolyte and the material, and improve the cycle performance of the battery. However, the electronic conductivity and electrical properties of the above-mentioned coating materials are still generally relatively low. Even if the lithium battery positive electrode material is doped and coated after optimization, the electrical properties of the lithium battery positive electrode material cannot be effectively improved. Summary of the invention

[0004] In response to the above technical problems, the present application provides a coated modified positive electrode material and a preparation method thereof, and a secondary battery.

[0005] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a coated modified positive electrode material is provided, comprising a positive electrode material substrate and a coating layer located on at least a portion of the surface of the positive electrode material substrate, wherein the coating layer is a composite material of La-doped MoP and carbon nanotubes.

[0006] In a second aspect, a method for preparing a coated modified positive electrode material is provided, comprising: (1) ammonium molybdate, lanthanum nitrate and ammonium dihydrogen phosphate are mixed and sintered in a mixed atmosphere of argon and hydrogen to obtain La-doped MoP powder; (2) adding carbon nanotubes to water and continuously stirring to obtain a mixed solution, then adding La-doped MoP powder to the mixed solution, dispersing the mixture, and centrifugally drying the mixture to obtain a composite material; (3) After the composite material is mixed with the positive electrode material, sintering is performed in an oxygen atmosphere to obtain a La-doped MoP and carbon nanotube composite coated modified positive electrode material.

[0007] In a third aspect, a secondary battery is provided, comprising the aforementioned coated modified positive electrode material or the coated modified positive electrode material prepared by the aforementioned preparation method.

[0008] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The use of La-doped molybdenum phosphide and carbon nanotube composites to coat modified positive electrode materials, especially high-nickel ternary positive electrode materials, can significantly improve the initial discharge capacity, rate performance and cycle performance of the battery.

[0009] The coating modification method is simple to operate and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0011] Figure 1 This is the SEM image of the La-MoP / CNT coated positive electrode material obtained in Example 1. DETAILED DESCRIPTION

[0012] The present invention provides a coated modified positive electrode material, comprising a positive electrode material matrix and a coating layer located on at least a portion of the surface of the positive electrode material matrix, wherein the coating layer is a composite material of La-doped MoP and carbon nanotubes.

[0013] Research has found that the La-doped MoP and carbon nanotube composite material coated with modified positive electrode materials can significantly improve their discharge specific capacity, rate performance and cycle performance.

[0014] Molybdenum phosphide (MoP) has a platinum-like electronic structure and high conductivity. La doping can precisely adjust the local electronic structure of the phosphide. The resulting material has good electronic or ionic conductivity, can adjust the electronic structure at the interface, introduce abundant oxygen vacancies, provide more active sites, and help accelerate the migration of electrons. La doping can refine MoP grains, increase its specific surface area and dispersibility; carbon nanotubes form multi-channel lithium ion transmission pathways, which can effectively improve the transmission efficiency of lithium ions and enhance the rate performance of positive electrode materials, thereby promoting charge transfer and structural integrity, and improving deficiencies such as low activity and poor conductivity. The La-doped MoP and carbon nanotube composite material is used to coat the modified cathode material. The La doping modification can refine the MoP grains, improve the dispersibility and specific surface area of ​​MoP, increase the contact area between the La-doped MoP and the carbon nanotubes and the modified cathode material, form a more stable interface structure, and thus improve the structural stability of the cathode material and improve the cycle performance. The La doping modification can improve the electronic conductivity of MoP, increase the specific surface area, and improve the dispersibility of the coating layer, which is beneficial to improving the dispersibility and composition uniformity of the coating layer, so that the composite material can be more evenly coated on the surface of the cathode material. The improvement of the composition uniformity of the composite material is beneficial to the advantages of the composite coating layer (i.e., the multi-channel lithium ion transmission pathway formed by the carbon nanotubes and the excellent electronic conduction of the La-doped MoP on the ion transmission and electron transmission of the cathode material), thereby obtaining an improvement effect on electrical performance that is better than that of a single coating.

[0015] In some preferred embodiments, the mass ratio of the coating layer to the positive electrode material matrix is ​​0.1%~0.5%:1.

[0016] In some preferred embodiments, in the coating layer, the mass ratio of carbon nanotubes to La-doped MoP is 0.1-0.3:1.

[0017] In some preferred embodiments, the molar ratio of La to Mo in the La-doped MoP is 0.04-0.06:6.65.

[0018] In some preferred embodiments, the chemical formula of the positive electrode material matrix is ​​LiNi x Co y Mn z O 2 , wherein 0≤x, y, z≤1, and x+y+z =1, and further preferably 0.6≤x<1, 0≤y≤0.4, 0≤z≤0.4.

[0019] The present invention provides a method for preparing a coated modified positive electrode material, comprising: (1) Mix the molybdenum source, lanthanum source and diammonium phosphate and heat them in an Ar / H 2Sintering is performed under a mixed atmosphere to obtain La-doped MoP powder; (2) adding carbon nanotubes to water and continuously stirring to obtain a mixed solution, then adding La-doped MoP powder to the mixed solution, dispersing the mixture, and centrifugally drying the mixture to obtain a composite material; (3) After the composite material is mixed with the positive electrode material, sintering is performed in an oxygen atmosphere to obtain a La-doped MoP and carbon nanotube composite coated modified positive electrode material.

[0020] In some preferred embodiments, the molar ratio of La contained in the lanthanum nitrate to Mo contained in the ammonium molybdate is 0.04-0.06:6.65.

[0021] In some preferred embodiments, the ratio of the total molar amount of Mo contained in the ammonium molybdate and the La contained in the lanthanum nitrate to the molar amount of ammonium dihydrogen phosphate is 7:6.94-7.06.

[0022] In some preferred embodiments, in step (1), the sintering temperature is 800-900° C. and the sintering time is 2-3 h.

[0023] Ar / H 2 The mixed atmosphere was commercially available Ar / H 2 Mixed gas, in which the concentration of hydrogen is 10%. Of course, you can also use your own prepared Ar / H 2 For the mixed gas, as long as the hydrogen concentration in the mixed gas meets the safety range and can achieve the reduction function, there are no other special requirements.

[0024] In some preferred embodiments, the mass ratio of La-doped MoP powder to carbon nanotubes is 0.1-0.3:1.

[0025] In some preferred embodiments, the mass ratio of the composite material to the positive electrode material is 0.1%~0.5%:1.

[0026] In some preferred embodiments, the chemical formula of the positive electrode material matrix is ​​LiNi x Co y Mn z O 2 , where 0≤x, y, z≤1, and x+y+z =1.

[0027] In some preferred embodiments, in step (2), the dispersion is ultrasonic dispersion. The process parameters of ultrasonic dispersion can be conventionally determined as long as a good dispersion effect in the liquid can be achieved.

[0028] In some preferred embodiments, in step (3), the sintering temperature is 500-600° C. and the sintering time is 5-7 hours.

[0029] In step (1) and step (3), mixing can be performed by conventional mixing methods in the art, as long as uniform mixing of the materials can be achieved, for example, dry mixing can be performed, wet mixing can be performed, ball milling can be performed, grinding can be performed, etc.

[0030] The present invention also provides a secondary battery, comprising the aforementioned coated modified positive electrode material or the coated modified positive electrode material prepared by the aforementioned preparation method.

[0031] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0032] Example 1 Weigh 0.95 mmol ammonium molybdate, 0.05 mmol lanthanum nitrate hexahydrate and 6.7 mmol ammonium dihydrogen phosphate and grind them into uniform powder; heat the powder prepared above at 900 °C, Ar / H 2 The La-doped MoP material was obtained by heating under the conditions of (10%) for 2 hours at a heating rate of 5°C / min.

[0033] Weigh CNTs and dissolve them in deionized water while stirring continuously. Slowly add the powder material prepared in step 1 into the above solution, where m CNTs :m La-MoP =0.2, ultrasonically controlled for 20 min and then centrifuged and dried to obtain the coated material La-MoP / CNT.

[0034] The obtained coating material is mixed with LiNi 0.9 Mn 0.1 O 2 Mix well in a mortar, the coating material is 0.3% of the mass of the positive electrode material, and the mixture is heated at 3 °C / min −1 The mixture was calcined at a heating rate of 600 °C in an oxygen atmosphere for 6 h, and finally La-MoP / CNT-coated lithium-ion battery positive electrode material was obtained.

[0035] Figure 1 This is the SEM image of the positive electrode material obtained in Example 1.

[0036] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that La-MoP / CNT is not coated.

[0037] Comparative Example 2 Weigh 0.95 mmol of ammonium molybdate (NH 4 )Mo 7 O 24 ·4H 2O), 0.05mmol lanthanum nitrate hexahydrate and 6.7mmol ammonium dihydrogen phosphate were fully ground into uniform powder; the powder prepared above was heated at 900℃, Ar / H 2 The La-MoP material was obtained by heating for 2 hours under the conditions of (10%) and a heating rate of 5°C / min.

[0038] The obtained La-MoP material was mixed with LiNi 0.9 Mn 0.1 O 2 Mix well in a mortar, La-MoP material is 0.3% of the mass of the positive electrode material, and the mixture is heated at 3 °C / min −1 The heating rate is 600℃ for O 2 After calcination in atmosphere for 6 hours, La-MoP-coated lithium-ion battery positive electrode material was finally obtained.

[0039] Comparative Example 3 CNTs and LiNi 0.9 Mn 0.1 O 2 Mix well in a mortar, CNTs is 0.3% of the mass of the positive electrode material, and the mixture is heated at 3 °C / min −1 The heating rate is 600℃ for O 2 After calcination in atmosphere for 6 hours, a CNT-coated lithium-ion battery positive electrode material was finally obtained.

[0040] Comparative Example 4 Weigh 1.0 mmol of ammonium molybdate and 7 mmol of ammonium dihydrogen phosphate and grind them into uniform powder; heat the powder prepared above at 900 °C, Ar / H 2 The MoP material was obtained by heating for 2 hours under the conditions of (10%) and a heating rate of 5°C / min.

[0041] Weigh CNTs and dissolve them in deionized water while stirring continuously. Slowly add the powder material prepared in step 1 into the above solution, where m CNTs :m MoP =0.2, ultrasonically control the temperature for 20 min, and then centrifugally dry to obtain the coated material MoP / CNT.

[0042] The obtained coating material is mixed with LiNi 0.9 Mn 0.1 O 2 Mix well in a mortar, the coating material is 0.3% of the mass of the positive electrode material, and the mixture is heated at 3 °C / min −1 The heating rate is 600℃ for O 2 After calcination in atmosphere for 6 hours, MoP / CNT-coated lithium-ion battery positive electrode material was finally obtained.

[0043] Example 2 Weigh 0.95 mmol ammonium molybdate, 0.05 mmol lanthanum nitrate hexahydrate and 6.65 mmol ammonium dihydrogen phosphate and grind them into uniform powder. Heat the powder at 800 °C and Ar / H 2 The La-MoP material was obtained by heating for 2 hours under the conditions of (10%) and a heating rate of 4°C / min.

[0044] Weigh CNTs and dissolve them in deionized water while stirring continuously. Slowly add the powder material prepared in step 1 into the above solution, where m CNTs :m La-MoP =0.1, ultrasonically control the temperature for 10 min and then centrifugally dry to obtain the coated material La-MoP / CNT.

[0045] The obtained coating material is mixed with LiNi 0.9 Co 0.06 Mn 0.04 O 2 Mix well in a mortar, the coating material is 0.1% of the mass of the positive electrode material, and the mixture is heated at 3 °C / min −1 The heating rate is 500℃ for O 2 After calcination in atmosphere for 5 h, La-MoP / CNT-coated lithium-ion battery positive electrode material was finally obtained.

[0046] Example 3 Weigh 0.95 mmol ammonium molybdate, 0.05 mmol lanthanum nitrate hexahydrate and 6.75 mmol ammonium dihydrogen phosphate and grind them into uniform powder. Heat the powder at 850 °C and Ar / H 2 The La-MoP material was obtained by heating for 2 hours under the conditions of (10%) and a heating rate of 6°C / min.

[0047] Weigh CNTs and dissolve them in deionized water while stirring continuously. Slowly add the powder material prepared in step 1 into the above solution, where m CNTs :m La-MoP =0.3, ultrasonically controlled for 30 min and then centrifuged and dried to obtain the coated material La-MoP / CNT.

[0048] The obtained coating material is mixed with LiNi 0.75 Mn 0.25 O 2 Mix well in a mortar, the coating material is 0.5% of the mass of the positive electrode material, and the mixture is heated at 3 °C / min −1 The heating rate is 550℃ for O 2 After calcination in atmosphere for 7 hours, La-MoP / CNT-coated lithium-ion battery positive electrode material was finally obtained.

[0049] The positive electrode materials of Examples 1 to 3 and Comparative Examples 1 to 4, and the uncoated modified NCM900604 and NM7525 positive electrode materials were assembled into batteries in the following manner: the positive electrode material, the binder PVDF, and the conductive agent were mixed in a ratio of 8:1:1, dry-milled for 10 min, and then the solvent NMP was added. After stirring evenly with a homogenizer, the positive electrode slurry was obtained, and the positive electrode slurry was evenly coated on an aluminum foil; a metal lithium sheet was used as a negative electrode; a lithium ion secondary electrolyte LB-037 (1M LiPF 6 in DEC:EC:EMC (volume ratio) = 1:1:1) as the electrolyte, Celgard2325 as the separator, assembled into LIR2032 button cell.

[0050] The electrical properties of the battery were tested in the following manner: in a 25°C constant temperature box, the battery was charged at a constant current of 0.1C to a voltage of 4.3V, then charged at a constant voltage of 0.01C and discharged at 0.1C to 3V, and the cycle was repeated twice. The battery was then charged at a constant current of 0.5C to a voltage of 4.3V, then charged at a constant voltage of 0.05C and discharged at 0.5C to 3V, and the charge and discharge capacity was recorded.

[0051] The test results are shown in Table 1. As can be seen from Table 1, the battery assembled with the positive electrode material prepared in Example 1 has significantly improved electrochemical performance and high stability compared with the battery assembled with the positive electrode material obtained in Comparative Example 1. Compared with Comparative Example 1, the positive electrode material prepared in Example 1 significantly improves the battery stability.

[0052] It can also be seen from Table 1 that the battery assembled with the positive electrode material prepared in Example 1 has significantly improved electrochemical performance and cycle stability compared with the battery assembled with the positive electrode material obtained in Comparative Example 4, which indicates that the modification of MoP in the coating layer by La effectively improves the electrochemical performance and structural stability of the positive electrode material. After analysis, this may be because: the modification and doping of La can adjust the local electronic structure of the phosphide, and the obtained material has good electronic or ionic conductivity, which can adjust the electronic structure at the interface; and the modification and doping of La can introduce abundant oxygen vacancies, provide more active sites, and help accelerate the migration of electrons.

[0053] It can also be seen from Table 1 that the battery assembled with the positive electrode material prepared in Example 1 has more significantly improved electrochemical performance and cycle stability than the batteries assembled with the positive electrode materials obtained in Comparative Examples 2 and 3, which indicates that the composite coating has a significantly better improvement in the electrochemical performance and structural stability of the positive electrode material than the single coating, that is, the composite coating produces a synergistic effect. After analysis, this may be because: La doping modification can refine the grains, increase the specific surface area of ​​MoP, increase the contact area between La doped MoP and carbon nanotubes and modified positive electrode materials, and form a more stable interface structure, thereby Improve the structural stability of the positive electrode material and improve the cycle performance; and La doping modification can improve the electronic conductivity of MoP, increase the specific surface area, and improve the dispersibility of the coating layer, which is beneficial to improve the dispersibility and composition uniformity of the coating layer, so that the composite material can be more evenly coated on the surface of the positive electrode material. The improvement in the composition uniformity of the composite material is conducive to the advantages of the composite coating layer (i.e., the multi-channel lithium ion transport pathway formed by carbon nanotubes and the excellent electronic conductivity of La-doped MoP modifying the ion transport and electron transport of the positive electrode material), thereby obtaining an improvement in electrical performance that is superior to a single coating.

[0054] It can also be seen from Table 1 that the composite coating has the effect of improving the electrical performance and structural stability of the positive electrode materials with different Ni contents, and this improvement is more obvious with the increase of Ni content.

[0055] Table 1 The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Coated modified positive electrode material, characterized in that: It comprises a positive electrode material matrix and a coating layer located on at least a part of the surface of the positive electrode material matrix, wherein the coating layer is a composite material of La-doped MoP and carbon nanotubes.

2. The coated modified positive electrode material according to claim 1, characterized in that: The mass ratio of the coating layer to the positive electrode material matrix is ​​0.1%~0.5%:1; In the coating layer, the mass ratio of carbon nanotubes to La-doped MoP is 0.1-0.3:1; The molar ratio of La to Mo in the La-doped MoP is 0.04-0.06:6.65; The chemical formula of the positive electrode material matrix is ​​LiNi x Co y Mn z O2, where 0≤x, y, z≤1, and x+y+z =1.

3. A method for preparing a coated modified positive electrode material, characterized in that: include: (1) mixing a molybdenum source, a lanthanum source and ammonium dihydrogen phosphate, and sintering them in a mixed atmosphere of argon and hydrogen to obtain La-doped MoP powder; (2) adding carbon nanotubes to water and continuously stirring to obtain a mixed solution, then adding La-doped MoP powder to the mixed solution, dispersing the mixture, and centrifugally drying the mixture to obtain a composite material; (3) After the composite material is mixed with the positive electrode material, sintering is performed in an oxygen atmosphere to obtain a La-doped MoP and carbon nanotube composite coated modified positive electrode material.

4. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: The ratio of the molar amount of La in the lanthanum source to the molar amount of Mo in the molybdenum source is 0.04-0.06:6.65; The lanthanum source is one or more of lanthanum nitrate and its hydrate, lanthanum acetate and its hydrate; The molybdenum source is one or more of ammonium molybdate and its hydrate, ammonium heptamolybdate and its hydrate.

5. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: The ratio of the total molar amount of Mo contained in the ammonium molybdate and the total molar amount of La contained in the lanthanum nitrate to the molar amount of ammonium dihydrogen phosphate is 7:6.94-7.

06.

6. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: In step (1), the sintering temperature is 800-900° C. and the sintering time is 2-3 hours.

7. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: The mass ratio of La-doped MoP powder to carbon nanotubes is 0.1~0.3:1; The mass ratio of the composite material to the positive electrode material is 0.1% to 0.5%:1; The chemical formula of the positive electrode material matrix is ​​LiNi x Co y Mn z O2, where 0≤x, y, z≤1, and x+y+z =1.

8. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: In step (2), the dispersion is ultrasonic dispersion.

9. The method for preparing a coated modified positive electrode material according to claim 3, characterized in that: In step (3), the sintering temperature is 500-600° C. and the sintering time is 5-7 hours.

10. A secondary battery, characterized in that: It includes the coated modified positive electrode material as described in claim 1 or 2 or the coated modified positive electrode material prepared by the preparation method as described in any one of claims 3 to 9.